Alzheimer’s disease-related presenilins are key to intestinal epithelial cell function and gut immune homoeostasis - Erkert, Lena; Gamez-Belmonte, Reyes; Kabisch, Melanie; Schödel, Lena; Patankar, Jay; Gonzalez Acera, Miguel; Mahapatro, Mousumi; Bao, Lili; Plattner, Christina; Kühl, Anja A.; Shen, Jie; Serneels, Lutgarde; et al. (Gut, 2024)
Objective Mutations in presenilin genes are the major cause of Alzheimer’s disease. However, little is known about their expression and function in the gut. In this study, we identify the presenilins Psen1 and Psen2 as key molecules that maintain intestinal homoeostasis. Design Human inflammatory bowel disease (IBD) and control samples were analysed for Psen1 expression. Newly generated intestinal epithelium-specific Psen1-deficient, Psen2-deficient and inducible Psen1/Psen2 double-deficient mice were used to dissect the functional role of presenilins in intestinal homoeostasis. Results Psen1 expression was regulated in experimental gut inflammation and in patients with IBD. Induced deletion of Psen1 and Psen2 in mice caused rapid weight loss and spontaneous development of intestinal inflammation. Mice exhibited epithelial barrier disruption with bacterial translocation and deregulation of key pathways for nutrient uptake. Wasting disease was independent of gut inflammation and dysbiosis, as depletion of microbiota rescued Psen-deficient animals from spontaneous colitis development but not from weight loss. On a molecular level, intestinal epithelial cells lacking Psen showed impaired Notch signalling and dysregulated epithelial differentiation. Conclusion Overall, our study provides evidence that Psen1 and Psen2 are important guardians of intestinal homoeostasis and future targets for barrier-promoting therapeutic strategies in IBD.
CRIS-Team Scopus Importer:2024-08-30

Analysis of the interferon-γ-induced secretome of intestinal endothelial cells: putative impact on epithelial barrier dysfunction in IBD - Naschberger, Elisabeth; Flierl, Christian; Huang, Jinghao; Erkert, Lena; Gámez Belmonte, Maria de los Reyes; Gonzalez Acera, Miguel; Bober, Magdalena; Mehnert, Martin; Becker, Christoph; Schellerer, Vera S.; Britzen-Laurent, Nathalie; Stürzl, Michael (Frontiers in Cell and Developmental Biology, 2023)
The development of inflammatory bowel diseases (IBD) involves the breakdown of two barriers: the epithelial barrier and the gut-vascular barrier (GVB). The destabilization of each barrier can promote initiation and progression of the disease. Interestingly, first evidence is available that both barriers are communicating through secreted factors that may accordingly serve as targets for therapeutic modulation of barrier functions. Interferon (IFN)-γ is among the major pathogenesis factors in IBD and can severely impair both barriers. In order to identify factors transmitting signals from the GVB to the epithelial cell barrier, we analyzed the secretome of IFN-γ-treated human intestinal endothelial cells (HIEC). To this goal, HIEC were isolated in high purity from normal colon tissues. HIEC were either untreated or stimulated with IFN-γ (10 U/mL). After 48 h, conditioned media (CM) were harvested and subjected to comparative hyper reaction monitoring mass spectrometry (HRM™ MS). In total, 1,084 human proteins were detected in the HIEC-CM. Among these, 43 proteins were present in significantly different concentrations between the CM of IFN-γ- and control-stimulated HIEC. Several of these proteins were also differentially expressed in various murine colitis models as compared to healthy animals supporting the relevance of these proteins secreted by inflammatory activated HIEC in the inter-barrier communication in IBD. The angiocrine pathogenic impact of these differentially secreted HIEC proteins on the epithelial cell barrier and their perspectives as targets to treat IBD by modulation of trans-barrier communication is discussed in detail.
CRIS-Team Scopus Importer:2023-09-08
Keywords: angiocrine; barrier; cytokines; endothelial; IBD-inflammatory bowel disease; interferon; paracrine; secretion

Breaking bad: necroptosis in the pathogenesis of gastrointestinal diseases - Patankar, Jay; Bubeck, Marvin; Gonzalez Acera, Miguel; Becker, Christoph (Frontiers in Immunology, 2023)
A delicate balance between programmed cell death and proliferation of intestinal epithelial cells (IEC) exists in the gut to maintain homeostasis. Homeostatic cell death programs such as anoikis and apoptosis ensure the replacement of dead epithelia without overt immune activation. In infectious and chronic inflammatory diseases of the gut, this balance is invariably disturbed by increased levels of pathologic cell death. Pathological forms of cell death such as necroptosis trigger immune activation barrier dysfunction, and perpetuation of inflammation. A leaky and inflamed gut can thus become a cause of persistent low-grade inflammation and cell death in other organs of the gastrointestinal (GI) tract, such as the liver and the pancreas. In this review, we focus on the advances in the molecular and cellular understanding of programmed necrosis (necroptosis) in tissues of the GI tract. In this review, we will first introduce the reader to the basic molecular aspects of the necroptosis machinery and discuss the pathways leading to necroptosis in the GI system. We then highlight the clinical significance of the preclinical findings and finally evaluate the different therapeutic approaches that attempt to target necroptosis against various GI diseases. Finally, we review the recent advances in understanding the biological functions of the molecules involved in necroptosis and the potential side effects that may occur due to their systemic inhibition. This review is intended to introduce the reader to the core concepts of pathological necroptotic cell death, the signaling pathways involved, its immuno-pathological implications, and its relevance to GI diseases. Further advances in our ability to control the extent of pathological necroptosis will provide better therapeutic opportunities against currently intractable GI and other diseases.
CRIS-Team Scopus Importer:2023-08-25
Keywords: caspase 8; inflammatory bowel disease; MLKL; necroptosis; RIPK3; therapeutic

Comparative Transcriptomics of IBD Patients Indicates Induction of Type 2 Immunity Irrespective of the Disease Ideotype - Gonzalez Acera, Miguel; Patankar, Jay; Diemand, Leonard; Siegmund, Britta; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Frontiers in Medicine, 2021)
Inflammatory cytokines initiate and sustain the perpetuation of processes leading to chronic inflammatory conditions such as inflammatory bowel diseases (IBD). The nature of the trigger causing an inflammatory reaction decides whether type 1, type 17, or type 2 immune responses, typically characterized by the respective T- helper cell subsets, come into effect. In the intestine, Type 2 responses have been linked with mucosal healing and resolution upon an immune challenge involving parasitic infections. However, type 2 cytokines are frequently elevated in certain types of IBD in particular ulcerative colitis (UC) leading to the assumption that Th2 cells might critically support the pathogenesis of UC raising the question of whether such elevated type 2 responses in IBD are beneficial or detrimental. In line with this, previous studies showed that suppression of IL-13 and other type 2 related molecules in murine models could improve the outcomes of intestinal inflammation. However, therapeutic attempts of neutralizing IL-13 in ulcerative colitis patients have yielded no benefits. Thus, a better understanding of the role of type 2 cytokines in regulating intestinal inflammation is required. Here, we took a comparative transcriptomic approach to address how Th2 responses evolve in different mouse models of colitis and human IBD datasets. Our data show that type 2 immune-related transcripts are induced in the inflamed gut of IBD patients in both Crohn's disease and UC and across widely used mouse models of IBD. Collectively our data implicate that the presence of a type 2 signature rather defines a distinct state of intestinal inflammation than a disease-specific pathomechanism.
CRIS-Team Scopus Importer:2021-06-25
Keywords: chronic inflammation; IBD; intestine; type 2 immunity; ulcerative colitis

Dynamic, transient, and robust increase in the innervation of the inflamed mucosa in inflammatory bowel diseases - Gonzalez Acera, Miguel; Bubeck, Marvin; Mascia, Fabrizio; Diemand, Leonard; Sturm, Gregor; Kuehl, Anja A.; Atreya, Raja; Lie, Dieter Chichung; Neurath, Markus; Schumann, Michael; Klose, Christoph S. N.; Trajanoski, Zlatko; et al. (Cells, 2021)
Inflammatory bowel diseases (IBD) are characterized by chronic dysregulation of immune homeostasis, epithelial demise, immune cell activation, and microbial translocation. Each of these processes leads to proinflammatory changes via the release of cytokines, damage-associated molecular patterns (DAMPs), and pathogen-associated molecular patterns (PAMPs), respectively. The impact of these noxious agents on the survival and function of the enteric nervous system (ENS) is poorly understood. Here, we show that in contrast to an expected decrease, experimental as well as clinical colitis causes an increase in the transcript levels of enteric neuronal and glial genes. Immunostaining revealed an elevated neuronal innervation of the inflamed regions of the gut mucosa. The increase was seen in models with overt damage to epithelial cells and models of T cell-induced colitis. Transcriptomic data from treatment naïve pediatric IBD patients also confirmed the increase in the neuroglial genes and were replicated on an independent adult IBD dataset. This induction in the neuroglial genes was transient as levels returned to normal upon the induction of remission in both mouse models as well as colitis patients. Our data highlight the dynamic and robust nature of the enteric nervous system in colitis and open novel questions on its regulation.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Crohn’s disease; Enteric nervous system; Inflammatory bowel diseases; Neurogenesis; Ulcerative colitis

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04
Keywords: colorectal cancer; colorectal adenomas; arachidonic and metabolism

Functional and spatial proteomics profiling reveals intra- and intercellular signaling crosstalk in colorectal cancer - Plattner, Christina; Lamberti, Giorgia; Blattmann, Peter; Kirchmair, Alexander; Rieder, Dietmar; Loncova, Zuzana; Sturm, Gregor; Scheidl, Stefan; Ijsselsteijn, Marieke; Fotakis, Georgios; Noureen, Asma; Lisandrelli, Rebecca; et al. (iScience, 2023)
Precision oncology approaches for patients with colorectal cancer (CRC) continue to lag behind other solid cancers. Functional precision oncology—a strategy that is based on perturbing primary tumor cells from cancer patients—could provide a road forward to personalize treatment. We extend this paradigm to measuring proteome activity landscapes by acquiring quantitative phosphoproteomic data from patient-derived organoids (PDOs). We show that kinase inhibitors induce inhibitor- and patient-specific off-target effects and pathway crosstalk. Reconstruction of the kinase networks revealed that the signaling rewiring is modestly affected by mutations. We show non-genetic heterogeneity of the PDOs and upregulation of stemness and differentiation genes by kinase inhibitors. Using imaging mass-cytometry-based profiling of the primary tumors, we characterize the tumor microenvironment (TME) and determine spatial heterocellular crosstalk and tumor-immune cell interactions. Collectively, we provide a framework for inferring tumor cell intrinsic signaling and external signaling from the TME to inform precision (immuno-) oncology in CRC.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Cancer; Cancer systems biology; Proteomics

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

Intestinal epithelial Gasdermin C is induced by IL-4R/STAT6 signaling but is dispensable for gut immune homeostasis - Gámez Belmonte, Maria de los Reyes; Wagner, Yara; Mahapatro, Mousumi; Wang, Ru; Erkert, Lena; Gonzalez Acera, Miguel; Cineus, Roodline; Hainbuch, Saskia; Patankar, Jay; Vöhringer, David; Hegazy, Ahmed N.; Neurath, Markus; et al. (Scientific Reports, 2024)
Gasdermin C is one of the least studied members of the gasdermin family of proteins, known for their critical involvement in pyroptosis and host defense. Furthermore, evidence for the role of Gasdermin C in the intestine is scarce and partly controversial. Here, we tested the functional role of Gasdermin C in intestinal homeostasis, inflammation and tumorigenesis. : We studied Gasdermin C in response to cytokines in intestinal organoids. We evaluated epithelial differentiation, cell death and immune infiltration under steady state conditions in a new mouse line deficient in Gasdermin C. The role of Gasdermin C was analyzed in acute colitis, infection and colitis-associated cancer. Gasdemin C is highly expressed in the intestinal epithelium and strongly induced by the type 2 cytokines IL-4 and IL-13 in a STAT6-dependent manner. Gasdermin C-deficient mice show no changes in tissue architecture and epithelial homeostasis. Epithelial organoids deficient in Gasdermin C develop normally and show no alterations in proliferation or cell death. No changes were found in models of acute colitis, type 2 intestinal infection and colitis-associated cancer. Gasdermin C genes are upregulated by type 2 immunity, yet appear dispensable for the development of intestinal inflammation, infection and colitis-associated cancer.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Gasdermin; Gut pathology; Intestinal homeostasis

Neutrophils prevent rectal bleeding in Ulcerative Colitis by peptidyl-arginine deiminase-4-dependent immunothrombosis - Leppkes, Moritz; Lindemann, Aylin; Goesswein, S.; Paulus, S.; Roth, Dominik; Hartung, A.; Liebing, Eva; Zundler, Sebastian; Gonzalez Acera, Miguel; Patankar, Jay; Mascia, Fabrizio; Scheibe, Kristina; et al. (JOURNAL OF CROHNS & COLITIS, 2022)
CRIS-Team WoS Importer:2022-05-13

PU.1-driven Th9 Cells Promote Colorectal Cancer in Experimental Colitis Models Through Il-6 Effects in Intestinal Epithelial Cells - Gerlach, Katharina; Popp, Vanessa; Wirtz, Stefan; Al-Saifi, Ragheed; Gonzalez Acera, Miguel; Atreya, Raja; Dregelis, Theresa; Vieth, Michael; Fichtner-Feigl, Stefan; Mckenzie, Andrew N. J.; Rosenbauer, Frank; Weigmann, Benno; et al. (Journal of Crohns & Colitis, 2022)
Background and Aims Colorectal cancer [CRC] is one of the most frequent malignancies, but the molecular mechanisms driving cancer growth are incompletely understood. We characterised the roles of the cytokine IL-9 and Th9 cells in regulating CRC development. Methods CRC patient samples and samples from AOM/DSS treated mice were analysed for expression of IL-9, CD3, and PU.1 by FACS analysis and immunohistochemistry. IL-9 citrine reporter mice, IL-9 knockout mice, and PU.1 and GATA3 CD4-Cre conditional knockout mice were studied in the AOM/DSS model. DNA minicircles or hyper-IL-6 were used for overexpression of cytokines in vivo. Effects of IL-6 and IL-9 were determined in organoid and T cell cultures. Claudin2/3 expression was studied by western blotting and bacterial translocation by FISH. Results We uncovered a significant expansion of IL-9- and PU.1-expressing mucosal Th9 cells in CRC patients, with particularly high levels in patients with colitis-associated neoplasias. PU.1(+) Th9 cells accumulated in experimental colorectal neoplasias. Deficiency of IL-9 or inactivation of PU.1 in T cells led to impaired tumour growth in vivo, suggesting a protumoral role of Th9 cells. In contrast, GATA3 inactivation did not affect Th9-mediated tumour growth. Mechanistically, IL-9 controls claudin2/3 expression and T cell-derived IL-6 production in colorectal tumours. IL-6 abrogated the anti-proliferative effects of IL-9 in epithelial organoids in vivo. IL-9-producing Th9 cells expand in CRC and control IL-6 production by T cells. Conclusions IL-9 is a crucial regulator of tumour growth in colitis-associated neoplasias and emerges as potential target for therapy.
CRIS-Team WoS Importer:2022-09-16

SMYD2 targets RIPK1 and restricts TNF-induced apoptosis and necroptosis to support colon tumor growth - Yu, Yidong; Thonn, Veronika; Patankar, Jay; Thoma, Oana-Maria; Waldner, Maximilian; Zielinska, Marta; Bao, Lili; Gonzalez Acera, Miguel; Wallmueller, Stefan; Engel, Felix; Stürzl, Michael; Neurath, Markus; et al. (Cell Death & Disease, 2022)
SMYD2 is a histone methyltransferase, which methylates both histone H3K4 as well as a number of non-histone proteins. Dysregulation of SMYD2 has been associated with several diseases including cancer. In the present study, we investigated whether and how SMYD2 might contribute to colorectal cancer. Increased expression levels of SMYD2 were detected in human and murine colon tumor tissues compared to tumor-free tissues. SMYD2 deficiency in colonic tumor cells strongly decreased tumor growth in two independent experimental cancer models. On a molecular level, SMYD2 deficiency sensitized colonic tumor cells to TNF-induced apoptosis and necroptosis without affecting cell proliferation. Moreover, we found that SMYD2 targeted RIPK1 and inhibited the phosphorylation of RIPK1. Finally, in a translational approach, pharmacological inhibition of SMYD2 attenuated colonic tumor growth. Collectively, our data show that SMYD2 is crucial for colon tumor growth and inhibits TNF-induced apoptosis and necroptosis.
CRIS-Team WoS Importer:2022-01-21